Research on Key Technologies of On-line Programming in Embedded System - Xuhui Chen; Dengyi Zhang; Hongyun Yang (2009 third International Symposium on Intelligent Information Technology Application : 21-22 November 2009, 2009)
In order to compensate for functional defects or add new features of an embedded product, the designer need to continuously update the system program. With the development of network technology, the end-user can download the update program through the network and complete the update process. But for the unattended equipments, they are often used of automatic remote update. On-line programming function is one of the most important parts for these equipments update. This paper discusses the key technologies for in-application programming in embedded systems, and gives an implementation example.